Assessment of the impact of procurement centralization on the drug provision for patients within the High-Cost Nosology Program in the Russian Federation - V. V. Omelyanovskiy; V. A. Ryagina; A. G. Kharitonova; K. I. Matrenin; A. A. Kingshott; O. V. Ashikhmina; M. V. Zhirov (Фармакоэкономика, 2024)
Background. In the Russian Federation, patients receive expensive drugs from the federal budget funds within High-Cost Nosology (HCN) Program.Objective: to assess the impact of drug procurement centralization on the weighted average price (WAP) per 1 unit of measurement (UM) of a drug, the procurement structure within HCN Program over 5 years (2019–2023), as well as the annual volume of procurements for each nosology and the additional annual growth compared to the previous year.Material and methods. The data on public procurement within HCN Program, regional and federal drug provision programs over the specified time period have been analyzed. During the analysis of individual nosologies, 22 drugs for the treatment of 12 HCN have been considered.Results. The median value of the change of WAP per 1 UM for all drugs within HCN Program was 6.01%. Aplastic anemia was characterized by the lowest volume of procurements over 5 years, while for malignant neoplasms was the largest. The growth in procurements from year to year within nosologies varied from +1% to +661%, while a decrease was from –97% to –1%.Conclusion. The results can be used as a basis for further research related to the process of implementation of preferential drug provision, and to development of additional tools to improve the efficacy of pharmacotherapy choice for included drugs and management decisions regarding the further expansion of HCN Program.